Keberlanjutan UMKM dan Utilisasi Potensi Destinasi Wisata Nagari Suliki Dalam Upaya Pemulihan Ekonomi Pasca Pandemi Covid-19 - Marsdenia Marsdenia (Universitas Negeri Padang, 2022)
The Covid-19 pandemic has shattered various joints of the social economy, both large companies and relatively smaller business entities such as (UMKM) or SMEs. This paper aims to explain conceptually how if the potential of Nagari Suliki tourist destinations can be utilized optimally, they will be able to synergize with MSMEs owned by the people of Nagari Suliki so that they will be able to quickly rise and survive after facing various difficult times during the Covid-19 pandemic. The answers to the paper questions were obtained through a descriptive analysis method of exposure by conducting several simulations of the utilization of the potential of Nagari Suliki's tourist destinations through data collection by observation, available data, and in-depth interviews with key informants such as Ninik Mamak, tribal leaders, communities and wali Nagari. The conclusion of this paper is that(UMKM) or SMEs in Nagari Suliki with various products, both culinary and non-culinary, can open a kind of booth or stand in various tourist destinations in Nagari Suliki so that visitors not only take selfies and enjoy the sights of existing tourist destinations but can also buy souvenirs, both typical food from Nagari Suliki and various souvenirs from Nagari Suliki